GERAKAN SHALAT DALAM TINJAUAN REFLEKSOLOGI - Mukhlasin Mukhlasin (INSPIRASI (Jurnal Kajian dan Penelitian Pendidikan Islam), 2023)
AbstractThe importance of the sociological approach to understanding religion is understandable because many religious teachings related to social problems. Jalaluddin Rahmat has shown how much attention to religion in this case is Islam against social problems. But today, the sociology of religion studying how religion affects the community, and may be religion maysrakat affect the concept of religion. Sociological Approaches have a very important role in efforts to understand and explore the true meanings intended by the Koran. Besides caused by Islam as a religion that prefers things that smelled of social rather than individual evidenced by the many verses of the Koran and the Hadith concerning muamalah affairs (social), it also caused a lot of stories in the Qur'an less can be understood properly unless with a sociological approach. Pentingnya pendekatan sosiologis dalam memahami agama dapat dipahami karena banyak sekali ajaran agama yang berkaitan dengan masalah sosial. Jalaludin Rakhmat telah menunjukkan betapa besarnya perhatian agama yang dalam hal ini adalah Islam terhadap masalah sosial. Namun dewasa ini, sosiologi agama mempelajari bagaimana agama mempengaruhi masyarakat, dan boleh jadi agama maysrakat mempengaruhi konsep agama. Pendekatan sosiologi memiliki peranan yang sangat penting dalam usaha untuk memahami dan menggali makna-makna yang sesungguhnya dikehendaki oleh alQur’an. Selain disebabkan oleh Islam sebagai agama yang lebih mengutamakan hal-hal yang berbau sosial daripada individual yang terbukti dengan banyaknya ayat al-Qur’an dan Hadis yang berkenaan dengan urusan muamalah (sosial), hal ini juga disebabkan banyak kisah dalam al-Qur’an yang kurang bisa dipahami dengan tepat kecuali dengan pendekatan sosiologi. Kata Kunci:  paradigma; sosiologis; Islam